2019
DOI: 10.3389/fgene.2019.00701
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rumen Microbial Genes Involved in Pathways Linked to Appetite, Growth, and Feed Conversion Efficiency in Cattle

Abstract: The rumen microbiome is essential for the biological processes involved in the conversion of feed into nutrients that can be utilized by the host animal. In the present research, the influence of the rumen microbiome on feed conversion efficiency, growth rate, and appetite of beef cattle was investigated using metagenomic data. Our aim was to explore the associations between microbial genes and functional pathways, to shed light on the influence of bacterial enzyme expression on host phenotypes. Two groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 93 publications
1
27
0
Order By: Relevance
“…To the best of our knowledge, only a limited number of studies like Lima et al (2019) identified microbial gene biomarkers for FCR and RFI. These authors applied a non-targeted approach for the selection of genes from metagenomics data.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only a limited number of studies like Lima et al (2019) identified microbial gene biomarkers for FCR and RFI. These authors applied a non-targeted approach for the selection of genes from metagenomics data.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the rumen microbiome composition of the adult cow was found to be connected with many of its host attributes and performance [8][9][10][11] . Recent studies, using metagenomic approaches, show that the rumen microbiome genes are associated with feed conversion processes, growth rate, and appetite [12][13][14] . Despite decades of research of the rumen microbiome, fundamental questions regarding its composition are still standing.…”
mentioning
confidence: 99%
“…Thus, when studying the rumen microbial ecosystem, cross-domain interactions between protozoa and prokarya need to be taken into consideration. 3…”
Section: Discussionmentioning
confidence: 99%
“…This process is performed by the highly complex microbial community residing in the first compartment of their digestive tract; the rumen. Accordingly, ruminant productivity is tightly linked with the rumen microbial community composition [2][3][4][5]. Several factors are known to impact the ruminal community including colonization history, diet, and host genotype [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%